Response of drip irrigated Broccoli (Brassica oleracea var. italica) in different irrigation levels and frequencies at field level (Journal of Applied and Natural Science, 2018)
Geometric increase in population coupled with rapid urbanization, industrialization and agricultural development are causing increased pressure on global water resources. Agriculture is the largest consumer of fresh water resources, thus the scope of enhancing water productivity in agriculture is taken to be the priority area of research. The right amount and frequency of irrigation is essential for optimum use of limited water resources for crop production as well as management. A field experiment with split plot design was carried out during November to February 2015-16 at PFDC (Precision Farming Development Centre), Water Technology Centre, IARI, New Delhi to study the effect of different irrigation levels and frequencies on Broccoli (Brassica oleracea var. italica) under drip irrigation. The experiment included three levels of irrigation frequencies: N1 (once every day), N2 (once every 2 days) and N3 (once every 3 days) with different irrigation levels of 100, 80 and 60 % of crop evapotranspiration (ETc). Results revealed that drip irrigation frequency significantly (p